Drag and inertia coefficients of live and surrogate shellfish dropper lines under steady and oscillatory flow. (1st September 2021) - Landmann, Jannis; Fröhling, Lukas; Gieschen, Rebekka; Buck, Bela H.; Heasman, Kevin; Scott, Nicholas; Smeaton, Malcolm; Goseberg, Nils; Hildebrandt, Arndt
Abstract: Against the background of a drastically increased demand of marine proteins, off-bottom, bivalve aquaculture, provides significant potential for production growth when moved into more energetic marine waters. Hence, research, industry and politics are currently proposing the development of new offshore sites. The highly energetic conditions at these sites present a challenging environment for bivalve aquaculture. In this work, physical experiments of suspended bivalves provide new knowledge on the commonly used design parameters: the drag and inertia coefficients. Live bivalves and manufactured surrogate models at a 1:1 scale were tested in a towing tank as well as under waves. The drag coefficient of live blue mussels was determined to be Cd = 1.6 for Reynolds numbers between 2.3 × 10 4 and 1.4 × 10 5 . The inertia coefficient obtained from the wave tests was Cm = 2.1 for Keulegan Carpenter numbers KC < 10. In a pursuit to better understand the differences between live mussels and surrogates in laboratory conditions, the analysis revealed that appropriate surrogates can be identified. A method to determine the characteristic diameter of mussel dropper lines is suggested. The results facilitate the future design of aquaculture systems in high-energy environments and allow for an integration into numerical models. Highlights: The loads a mussel dropper is subjected to in offshore environments are separated and studied using physical model tests. Drag C D and inertia C M coefficients of live/surrogate dropper lines under steady and oscillatory conditions are considered. A drag coefficient of CD = 1.6 is recommended for currents with subcritical flow regimes ( R e < 10 ˆ 5 ) and blue mussels. Under oscillatory conditions a drag coefficient of CD = 2.3 and an inertia coefficient of CM = 2.1 are proposed for KC < 10. This study shows that the choice of the characteristic diameter has a large influence on the hydrodynamic coefficients.